UPAYA WORLD HEALTH ORGANIZATION (WHO) DALAM MENGATASI PEREDARAN OBAT PALSU DI INDONESIA - Firdaus, Deksha Putri; Yealta, Den (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The fact that Indonesia is one of the country that prone of falsified medicine entry, development of its industry and is the country with the highest number of falsified medicines for low-middle income countries were indeed unavoidable again. The problem of falsified medicines a threat so real and very contradictory for Indonesia who wants to realizing the realization of high quality of Indonesian human being, the advanced and prosperous life. Referring to the increasing intensity of falsified medicines which gets higher throughout the year and not balanced by adequate handling, then some efforts to overcoming the circulation of falsified medicines are very much needed by Indonesia today, one of them by joining and conducting international cooperation with the World Health Organization (WHO).This research uses the rule of international organization theory, the perspective of pluralism and supported by the concept of Non-traditional security. This study also uses qualitative descriptive research methods and uses level of group behavior analysis. Research data is obtained through the literature review and all research data derived directly from the government official website and related organizations.Based on the results from analyzing of the researchers, it can be concluded that the efforts of the World Health Organization (WHO) to overcoming the circulation of falsified medicines in Indonesia is through the establishment of Member State Mechanism (MSM) which is realized by drafting and Run the Action Plan that was created by MSM and then it adopted into National Action by Indonesia. This research proves that the Indonesian Government has a strong commitment and is trying to overcoming the circulation of falsified medicines for the realization of human security for Indonesian people. Keywords: World Health Organization (WHO), Member State Mechanism (MSM), Effort, Falsified Medicines, BPOM.